Medical Liability and Liability of Health Institutions in Turkish Law - Özsunay, Ergun (Brill Publishers, 2007)
This article deals with medical liability of doctors and health institutions under Turkish law. Medical liability is based usually on a medical treatment agreement. This agreement is qualified as "mandate" (Auftrag). Under this agreement doctors are obliged to carry out medical intervention and treatment in accordance with professional standards. Informed consent is a prerequisite for all medical interventions. Treatment without patient's informed consent is a ground of liability. As regards treatment in hospitals medical treatment agreement is concluded between patient and hospital management. Doctors and other health care personnel employed by private hospitals are auxiliaries in medical treatment. Liability for treatment in State or municipality hospitals is based on administrative law. In case of malpractice, liability of physicians and health institutions covers all bodily injuries and material damages as well as immaterial damages. A draft law on liability for malpractice in medical services is being discussed by relevant circles in Turkey.
Keywords: Sağlık hukuku; Sorumluluk; Sağlık kurumlarının hukuki sorumluluğu